Repeated Cocaine Administration Attenuates Group I Metabotropic Glutamate Receptor-Mediated Glutamate Release and Behavioral Activation: A Potential Role for Homer - Swanson, Chad J. (J Neurosci, 2001)
The present study aimed to characterize a functional role for group I metabotropic glutamate receptors (mGluRs) in the nucleus accumbens and the capacity of repeated cocaine to elicit long-term changes in group I mGluR function. Reverse dialysis of the group I agonist (RS)-3,5-dihydroxyphenylglycine (DHPG) into the nucleus accumbens resulted in an increase in extracellular glutamate levels that was mediated by the mGluR1 subtype and depended on voltage-dependent Na(+) and Ca(2+)conductance. At 3 weeks after discontinuing 1 week of daily cocaine injections, the capacity of DHPG to induce glutamate release was markedly reduced. Similarly, DHPG induced an mGluR1-dependent increase in locomotor activity after microinjection into the nucleus accumbens that was significantly blunted 3 weeks after repeated cocaine administration. Signaling through group I mGluRs is regulated, in part, by Homer proteins, and it was found that the blunting of group I mGluR-induced glutamate release and motor activity after repeated cocaine was associated with a reduction in Homer1b/c protein that was selective for the medial nucleus accumbens. These data show that repeated cocaine produces an enduring inhibition of the neurochemical and behavioral consequences of stimulating mGluR1 that is accompanied by changes in the mGluR scaffolding apparatus.